Respuesta :
9514 1404 393
Answer:
f^-1(x) = ∛((x +5)/2)
Step-by-step explanation:
Continue to solve for y.
[tex]x +5=2y^3\qquad\text{so far so good}\\\\\dfrac{x+5}{2}=y^3\qquad\text{divide by 2}\\\\\sqrt[3]{\dfrac{x+5}{2}}=y\qquad\text{take the cube root}\\\\\boxed{f^{-1}(x)=\sqrt[3]{\dfrac{x+5}{2}}}\qquad\text{expressed in functional form}[/tex]
If you want to "rationalize the denominator", you can multiply both numerator and denominator by 4 inside the radical. This will simplify to ...
[tex]\displaystyle\boxed{f^{-1}(x)=\frac{1}{2}\sqrt[3]{4x+20}}[/tex]
- y be f(x)
[tex]\\ \rm\Rrightarrow y=2x^3-5[/tex]
- Interchange y and x
[tex]\\ \rm\Rrightarrow x=2y^3-5[/tex]
[tex]\\ \rm\Rrightarrow 2y^3=x+5[/tex]
- Isolate y
[tex]\\ \rm\Rrightarrow y^3=\dfrac{x+5}{2}[/tex]
[tex]\\ \rm\Rrightarrow y=\sqrt[3]{\dfrac{x+5}{2}}[/tex]
- This is the inverse
[tex]\\ \rm\Rrightarrow f^{-1}(x)=\sqrt[3]{\dfrac{x+5}{2}}[/tex]